Optimalisasi Layanan Bimbingan Kelompok untuk Meningkatkan Kebiasaan Siswa Bertanya dalam Proses Pembelajaran di SMK Negeri 4 Gowa - H Burhanuddin (Jurnal Paedagogy, 2021)
The purpose of this study is to improve the habit of asking students in the learning process through the optimization of group guidance services. This research method uses classroom action research. The research procedure consists of planning, acting, observing and reflecting in 3 cycles. The subjects of this study were 10 students of class XI TKJ 2 SMK Negeri 4 Gowa. The research data collection technique used observation and questionnaires. While the data analysis in this study used a qualitative descriptive consisting of data processing, data analysis, and data presentation. The results of this study indicate that there is an increase in the habits of students in asking through the optimization of group guidance services. The increase in the habit of asking can be seen from the results of observations during the action process in group guidance activities, namely the existence of demands to display questioning behavior, the form of questioning behavior that is displayed is spontaneous, can choose the right time to ask and ask well without offending other people's feelings. As supporting data, to determine the increase in the habit of asking questions is through observations made by counseling teachers and subject teachers as a comparison. The result of the class is that there is an increase in the habit of asking in the learning process gradually from cycles 1, 2 and 3. In cycle 1 the frequency of asking questions is 40%, cycle II is 60% and in cycle III there is 80%. Thus through the optimization of group guidance services can increase the activeness of asking group members in the learning process.